PERLAKUAN AKUNTANSI UNTUK SISA BAHAN BAKU (STUDI KASUS PTPN I UNIT PKS TANJUNG SEUMANTOH ACEH TAMIANG) - Nurdiansyah, Muhammad; Afrinandra, Cut (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
The purpose of this research is to know how the accounting treatment for the scrap materials at PTPN 1 unit PKS Tanjung Seumantoh Aceh Tamiang. The scrap material from the palm oil production process at PTPN 1 unit PKS Tanjung Seumantoh Aceh Tamiang are in the form of palm shells and fiber. The type of this research is qualitative research with descriptive analysis method. The result of shows that the scrap material for palm kernel shells was recognized as other income and presented in the companys income statement, while fiber was used as boiler fuel as well as a reduction in manufacturing overhead costs